Access to flexible work arrangements, working-time fit and job satisfaction - Daniel S. Possenriede; Janneke Plantenga (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2011)
This article analyses the effects of access to flexible work arrangements, namely flexi-time, telehomework and part-time work, on employees' satisfaction with the fit between paid work and private life and their overall job satisfaction. Having access to flexible work arrangements gives employees more control over their working life and thereby improves on the match between paid work and private life. Based on unique cross-sectional survey data collected among more than 20.000 Dutch public sector employees the results show that access to flexible work arrangements, especially flexi-time, is associated with sizeable increases in satisfaction with working-time fit and overall job satisfaction. Somewhat surprisingly, the effects hardly differ between male and female employees and between employees with and without children. Flexible work arrangements apparently appeal not only to employees with family responsibilities but more general to all employees.
Keywords: 330; flexi-time; flexible work arrangements; job satisfaction; part-time work; telehomework; working-time fit